Writing and presenting in English : the Rosetta Stone of science - Young, Petey (Elsevier, 2006)
The Rosetta Stone of Science is a useful and practical guide to presenting scientific research in the English language. It is written specifically for scientists who would like to improve the effectiveness with which they use the English language and improve their communicative skills in order to become published and develop more confidence in presenting their work at international conferences. Part 1 of the book covers the style preferred by today's leading journals, discusses how to prepare models for writing research papers, and provides advice for writing abstracts, proposals, and editing. Examples of cover letters are also given. Part 2 discusses the various arts and techniques used by successful presenters at scientific conferences. The content of the book is presented in a light, simple and informative manner making The Rosetta Stone of Science an entertaining and instructive read. This book will prove invaluable to all scientists, research fellows, post-docs, and graduate students whose first language is not English.